Luteal phase serum progesterone level: a potential predictive marker for pregnancy rate in intracytoplasmic sperm injection. - Gumaa, Shaimaa S.; Almadfa, Zaid A.; Al-Aboudy, Nada F. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: It is evident that there is a lack of clear consensus on the role of luteal phase serum Progesterone (P) level in the prediction of early pregnancy after controlled ovarian hyperstimulation (COH) protocols in assisted reproductive techniques (ART).Objective: We conducted this study in order to investigate the potential value of luteal phase serum progesterone measurement, in women undergoing ICSI treatment cycles and receiving progesterone supplements, in relation to pregnancy rate.Patients: A total of 68 women aged 20-40 years undergoing their first intracytoplasmic sperm injection (ICSI) cycles in fertility and I.V.F center of Kamal Al samrai hospital.Methods: women consecutively treated by ICSI had Estimation of luteal phase serum Progesterone levels on days 0 and 14 of embryo transfer (ET).Results: 10 pregnancies were achieved (14.7%). Age, basal FSH level, peak E2 level, number of oocytes retrieved, and number of embryos transferred were comparable between pregnant and nonpregnant women. Day-0 and day-14 luteal phase serum Progesterone levels were significantly different between the two groups.Conclusion: Luteal phase serum Progesterone concentration seems to be a promising marker for prediction of early pregnancy in intracytoplasmic sperm injection.